Rokok dan Sirih sebagai simbol budaya dalam prosesi pernikahan adat Batak Angkola - Ali AlFauzan; Susi Fitria Dewi; Fatmariza Fatmariza; Oktaviani Puspita Sari (Departemen Pendidikan Kewarganegaraan dan Ilmu Hukum Universitas Negeri Padang, 2026)
This study aims to analyze the mechanism and stages of the Batak Angkola traditional wedding ceremony and to examine the symbolic meanings of cigarettes and betel (burangir) within the cultural context of society. This research is motivated by the importance of understanding cultural symbols that persist amid modernization, although their meanings are gradually shifting among younger generations. The study employs a qualitative approach with a descriptive method to explore symbolic meanings in depth based on the perspectives of cultural actors directly involved in the tradition. Data collection techniques include observation, in-depth interviews, and documentation involving purposively selected informants, including traditional leaders, religious figures, women, and youth. Data analysis uses the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, while data validity is ensured through source and method triangulation. The results show that the traditional wedding process consists of several stages, namely manyapai boru, marpege-pege, manulak sere hasahatan, culminating in horja and mangupa. Each stage contains symbolic meanings that reflect social and cultural values within the community. Cigarettes are interpreted as symbols of respect, communication, and social bonding, while betel (burangir) represents acceptance, affection, and kinship ties. Both function as nonverbal communication media that strengthen social and cultural values while maintaining the continuity of traditions and reinforcing local cultural identity amid ongoing social change.